The THE INFLUENCE OF SOCIAL MEDIA MARKETING AND BRAND TRUST ON REPURCHASE INTENTION THROUGH CUSTOMER SATISFACTION AS AN INTERVENING VARIABLE AT FOODPEDIA X KOPI DARI HATI METLAND CILEUNGSI - Hasanah, Putri Aprilia; Harini, Sri; Yulianingsih (Universitas Ciputra Surabaya, 2025)
This study looks into Foodpedia X Kopi Dari Hati Metland Cileungsi's customer satisfaction in order to ascertain how social media marketing and brand trust impact repurchase intention. A survey was completed by 100 clients, and the data was analyzed using the path analysis method in IBM SPSS version 25. According to the study's findings, social media marketing and brand trust have an impact on repurchase intention, which may then be mediated by customer satisfaction. It is suggested that the company tailor its social media posts to the individual characteristics of each client in light of these findings., ensure consistent product and service quality, introduce menu innovations, and highlight the uniqueness or distinctive features of the restaurant and café. Keywords: Social Media Marketing, Brand Trust, Customer Satisfaction, Repurchase Intention, Path Analysis.